Liver stiffness is associated with disease severity and worse clinical scenarios in coronavirus disease 2019: A prospective transient elastography study. Issue 9 (29th May 2021) - Demirtas, Coskun Ozer; Keklikkiran, Caglayan; Ergenc, Ilkay; Erturk Sengel, Buket; Eskidemir, Gunes; Cinel, Ismail; Odabasi, Zekaver; Korten, Volkan; Yilmaz, Yusuf
Abstract: Background: Pre‐existing chronic liver disease is currently considered a poor prognostic factor for coronavirus disease 2019 (COVID‐19). The present study aimed to investigate the association of liver stiffness measurement (LSM) with disease severity and clinical course of COVID‐19. Methods: We prospectively recruited consecutive hospitalised adult patients with COVID‐19 in a 3‐month period. Demographic, laboratory, clinical and vibration‐controlled transient elastography (VCTE) features were recorded at entry, and all patients were prospectively followed‐up. Severe liver fibrosis was defined as an LSM value higher than 9.6 kPA. Multivariate logistic regression analysis was performed to reveal factors associated with disease severity and outcomes. Results: Out of 98 eligible patients with COVID‐19, 12 (12.2%) had severe liver fibrosis. Patients with severe liver fibrosis had higher baseline disease severity ( P = .022), more commonly required oxygen treatment at entry ( P = .010), and had intensive‐care unit (ICU) requirements during the 6 (1‐39)‐day median follow‐up time ( P = .017). The presence of severe liver fibrosis was independently associated with disease severity (odds ratio (OR): 7.685, 95% confidence interval (CI): 1.435‐41.162, P = .017) and ICU requirement (OR: 46.656, 95% CI: 2.144‐1015.090, P = .014). LSM was correlated with alanine aminotransferase levels ( P = .005, r: 0.283), but not with other markers of acute hepatic injury or inflammation. Conclusion: Initial VCTE application might help physicians identify patients who are more likely to have severe illness or worse clinical outcomes, in addition to other well‐established clinical and laboratory factors. Further multicentre prospective studies are warranted to validate our results.